Melt Cheezy Bol / Salbiah Samat - Samat, Salbiah (2019)
'Ask for Bol' is a trademark for our Melt Cheezy Bol. The main objective that is to achieve for the business is to offer variety of Melt Cheezy Bol to our customer with affordable price and luxurious taste of Malaysia. Our business was started on 1st of October in 2019. According to the customer review, our product gave a fantastic taste because the tangy of the Melt Cheezy Bol make our customer remembered the taste. This product is also liked by many due to the cheap and affordable price. Hence, this product provides a good insight for the continuation of sale to our customers. Since early of its opening, Melt Cheezy Bol was sold more than more than 20 packages for with cheezy flavour. Increasing demands for our product results into a good profitable sale revenue to my business project. Therefore, Melt Cheezy Bol is a good marketable product of choice that can be further expanded to many different areas as the business keeps on growing. The management of Melt Cheezy Bol consists of two workers is Salbiah Binti Samat and my sister, Siti Aisyah Binti Samat. I also created Facebook to expand my business through social media and learn how to post Facebook post for business product whether teaser post, soft sell and hard sell. I also must raise the revenue at least RM 50 and above and prudent spending my product to avoid profit falls. Furthermore, I have service and products commitments plan to promote the product.